2009
DOI: 10.1186/1477-9560-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of VerifyNow-P2Y12 test and Flow Cytometry for monitoring individual platelet response to clopidogrel. What is the cut-off value for identifying patients who are low responders to clopidogrel therapy?

Abstract: Background: Dual anti-platelet therapy with aspirin and a thienopyridine (DAT) is used to prevent stent thrombosis after percutaneous coronary intervention (PCI). Low response to clopidogrel therapy (LR) occurs, but laboratory tests have a controversial role in the identification of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…This value indicates the level of active clopidogrel metabolite-P2Y12 receptor interaction, which inhibits platelet aggregation. 18 According to the manufacturer's manual, percentage inhibition is derived by the VerifyNow P2Y12 assay from the platelet reactivity unit (PRU) and baseline platelet thrombosis activity (BASE). The formula used to calculate percentage inhibition is Percentage Inhibition ϭ (BASE Ϫ PRU) ϫ 100/BASE.…”
Section: Ex Vivo Clopidogrel Response Testingmentioning
confidence: 99%
“…This value indicates the level of active clopidogrel metabolite-P2Y12 receptor interaction, which inhibits platelet aggregation. 18 According to the manufacturer's manual, percentage inhibition is derived by the VerifyNow P2Y12 assay from the platelet reactivity unit (PRU) and baseline platelet thrombosis activity (BASE). The formula used to calculate percentage inhibition is Percentage Inhibition ϭ (BASE Ϫ PRU) ϫ 100/BASE.…”
Section: Ex Vivo Clopidogrel Response Testingmentioning
confidence: 99%
“…Recently, easier and more accurate assays such as the VerifyNow® P2Y12 assay have become standard in many hospital settings, as in ours [45][46][47]. This test prevents nonspecific activation of platelets and corrects for baseline platelet activity, making this test more specific for the inhibition from clopidogrel [48]. The VerifyNow® P2Y12 correlates well with levels of clopidogrel in the plasma and has thus been reported as one of the most accurate assays of platelet activity in response to the drug [45].…”
Section: Discussionmentioning
confidence: 99%
“…Shim et al reported that the rate of clopidogrel resistance (defined as a percent inhibition <20%) was 40%. 28 Godino et al reported that the rate of clopidogrel resistance defined as a % inhibition of ≤15% was 21% 34 . The wide variation is also partly because of the difference between investigators' options regarding the cut-off value which should be considered as suboptimal and also because of the different time interval taken between drug intake and measurement of blood samples.…”
Section: Discussionmentioning
confidence: 99%